PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING TERHADAP PEMAHAMAN KONSEP DAN BERPIKIR KRITIS SISWA DI SDN 151 SUKASENANG BANDUNG - Raden Deby Cyntia Dinanti; Yusuf Ibrahim; Sopyan Hendrayana (STKIP Subang, 2023)
This study aims to determine the effect of using the problem based learning model on students' conceptual understanding and critical thinking at SDN 151 Sukasenang Bandung. This study used a quasi-experimental type of nonequivalent control group design. The population used in this study were all fifth grade students at SDN 151 Sukasuka Bandung, consisting of 55 students. The samples of this study were two groups, 28 students in class VA as the experimental class, while in class 5 B there were 27 students as the control class. In the experimental class the treatment being taught is in the form of using a Problem Based Learning model. In this study the results showed that the Problem Based Learning mode had an effect on students' conceptual understanding and critical thinking at SDN 151 Sukasuka Bandung. It can be seen from the effect size test results of 1.67 it can be said to get a large value so that it can be concluded that there is a large influence on students' critical thinking.